1977
DOI: 10.1115/1.3426276
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of the Fluid Dynamics of Multiple Noncritical Stenoses

Abstract: The effects of the number of stenoses and the distance between consecutive stenoses on the total pressure drop across a series of noncritical stenoses with 50 percent area reduction were determined experimentally. The mean flow rate was varied to correspond to a Reynolds number range of 30–280 and both in vitro and in vivo measurements of the pressure drop were carried out. Flow visualization studies also were performed. The pressure drop across a series of stenoses was found to increase linearly with the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 0 publications
5
21
0
Order By: Relevance
“…Again the features similar to those observed at Re = 1200 are clearly noticed at Re = 800 and mildly at Re = 200. At Re = 100 no ow separation is noticed on the diverging walls of both the constrictions and is exactly in agreement with the experimental observations of Talukder et al [13].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Again the features similar to those observed at Re = 1200 are clearly noticed at Re = 800 and mildly at Re = 200. At Re = 100 no ow separation is noticed on the diverging walls of both the constrictions and is exactly in agreement with the experimental observations of Talukder et al [13].…”
Section: Resultssupporting
confidence: 91%
“…When these constrictions are positioned close to one another, they would be expected to interact with each other and their combined e ect could be di erent from the non-interacting case. Talukder et al [13] and Van Dreumel and Kuiken [14] have carried out experimental studies related to ow dynamics in doubly contricted vessels. Recently, Lee [15] and Damodaran et al [16] have made 2D steady ow computational analysis of ow in multiply constricted vessels.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum contribution of the SGS model also increases at the region of the second stenosis. The upper wall pressure drops and wall shear stress increase rapidly in the region of stenoses for increasing the Reynolds numbers, which are consistent with the results of Talukder et al [15] and Damodaran et al [9]. It is clearly seen that the maximum pressure drops and wall shear stress occur due to the effects of the second stenosis.…”
Section: Discussionsupporting
confidence: 90%
“…One experimental investigation was done by Talukder et al [15] to study the effects of multiple stenoses on the pressure drop for various Reynolds numbers ranging from 30 to 280. They reported that the intensity of pressure drop increases owing to the presence of multiple stenoses.…”
Section: Introductionmentioning
confidence: 99%
“…In that case, viscous friction, as accounted for in the first term of these equations, would cause the major pressure loss, since length would be large, and the second term, reflecting exit pressure loss, would be fairly small in the absence of a discrete lesion. As a variation of this same question, the combined effects of multiple stenoses in series can be accounted for by appropriate fluid dynamic analysis Talukder et al, 1977).…”
Section: Relation Between Anatomic and Functional Characteristics Of mentioning
confidence: 99%